Aerial phytomass survey of the Casa de Piedra reservoir dam basin area (Semiárida, 2020)
In an area of shrublands in the southwest of La Pampa we determined woody aerial phytomass and density of shrubs. The results obtained in the area I (Aquatic), II (amphibiam) and III (rarely inundated) were 11.000, 12.000 and 13.000 k/ha respectively. Density of Larrea cuneifolia were 979, 1.686 and 1.736 pI /ha in the areas I, II y III. Atriplex lampa had 670. 1079 and 933 pI/ha. Larrea divaricata had 357, 894 and 913 pl/ ha in the threee different areas. The principal units of vegetation were: a shrubland of Larrea cuneifolia, a shrubland of Larrea divaricata and a Heathland of Suaeda divaricata and Atriplex ondulata. A tall grassland of Cortadera selloana was present on the sandy soils.